A first record of Cretaceous aphids (Hemiptera, Sternorrhyncha, Aphidomorpha) in Australia, from the Lower Cretaceous Koonwarra Fossil Bed, Victoria - Martin, Sarah K.; Skidmore, Luke I.; Stilwell, Jeffrey D. (Zootaxa, 2016)
This paper describes the first species of aphid from the Lower Cretaceous Koonwarra Fossil Bed of the Gippsland Basin, southeastern Victoria, Australia. This aphid, herein named Koonwarraphis rotundafrons gen. & sp. nov., is assigned to the cosmopolitan Cretaceous superfamily Tajmyraphidoidea, which has been previously described from the Lebanese, Taimyrian, Canadian, Myanmar (Burmese), and Spanish ambers. Koonwarraphis rotundafrons is the first aphid recorded from the eastern Gondwanan landmass during the Cretaceous, and represents the only tajmyraphidoid preserved as a compression fossil, rather than as an amber inclusion. Due to the nature of the fossil’s preservation, Koonwarraphis cannot be firmly placed in any of the described tajmyraphidoid families; however, all observable morphological features suggest that the genus is broadly typical of the superfamily and Cretaceous aphids in general. Koonwarraphis’ shortened rostrum, a feature also seen in other tajmyraphidoids, suggests an association with the more herbaceous aspects of the Early Cretaceous Victorian flora. Considering the modern aphid preference for angiosperm plants, it is possible that this aphid was living upon the herbaceous early angiosperms recorded previously from the Koonwarra macrofloral assemblage.